Is the Digital Economy Driving the Economic Growth of the Sumatra Region During the Pandemic? - Adhitya Wardhono; M. Abd. Nasir; Ariz Aprilia; Panji Tirta Nirwana Putra; Ben Hansel N. Zebua (Universitas Muhammadiyah Yogyakarta, 2022)
Digitalization has an essential role during the pandemic because it helps facilitate various economic activities. This study aims to analyze the economic digitization of financial technology on economic growth in the Sumatra region (North Sumatra, West Sumatra, and South Sumatra) in January 2020-June 2021. We also used macroeconomic indicators in the form of inflation, foreign direct investment (FDI), and domestic investment (DI) as a control to explain economic conditions. The analysis results using the Panel Vector Autoregression (P-VAR) showed that fintech contributed positively to economic growth. This result was supported by maintained inflation stability that created a conducive investment climate, thereby attracting FDI. We recommend that the regional government take advantage of existing fintech and that